Amador (1979), de Krzysztof Kieslowski, e o cine-olho de Dziga Vertov - MELLO, Davi Marques Camargo de (2018)
Starting out working with documentaries on short films, the Polish filmmaker Krzysztof Kieślowski achieved international status with his second fiction feature, Camera Buff (Amator, 1979), centered on a factory worker who acquires a cinematographic camera and perceives it as a new eye capable of exposing contradictions in the sociopolitical context around him. With that in mind, and with a focus on film ethics and aesthetics, this research seeks a similarity of Kieślowski's feature film with the concept of kino-eye conceived by the Soviet filmmaker Dziga Vertov, a disciplinary method of view that focuses on capturing life unawares and filmic reflexivity. The camera on Camera Buff is quite singular, due to the director's choice for a device that does not differentiate textures, merging his own camera with the one handled by the protagonist Filip Mosz (Jerzy Sthur). The duplicity of the camera, cultivated by the montage, creates a uniform and autonomous illusion, thus becoming a resource for self-reflection about filmmaking, working as a political metaphor while producing private records and granting power to the average person – elements that also mark Vertov’s work, whose principles are linked to a social understanding of the world and the images.